2022
DOI: 10.3389/fpsyg.2022.996559
|View full text |Cite
|
Sign up to set email alerts
|

Does the practice of mindfulness reduce somatic symptoms and COVID-19-related anxiety? A community-based survey

Abstract: ObjectiveSince the beginning of COVID-19 pandemic, several studies have shown an increase of psychological distress in the general population. Previous research demonstrated that high levels of anxiety are associated with reporting more somatic symptoms. The ability to adaptively regulate emotions is essential to deal with stressful situations, and it is one of the main components of mindfulness practice. The aim of the present study was to document the effect of mindfulness practice on somatic symptoms and ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 80 publications
0
0
0
Order By: Relevance
“…Further supporting this, Micheli et al (2022) found that mindfulness practices significantly reduced somatic symptoms and COVID-19-related anxiety in a communitybased survey. These findings suggest that mindfulness interventions like MBSR can be particularly beneficial in times of heightened stress, such as during a pandemic (Micheli et al, 2022). The ability to remain present and observe physical sensations without excessive worry may help mitigate the stress-related exacerbation of somatic symptoms.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Further supporting this, Micheli et al (2022) found that mindfulness practices significantly reduced somatic symptoms and COVID-19-related anxiety in a communitybased survey. These findings suggest that mindfulness interventions like MBSR can be particularly beneficial in times of heightened stress, such as during a pandemic (Micheli et al, 2022). The ability to remain present and observe physical sensations without excessive worry may help mitigate the stress-related exacerbation of somatic symptoms.…”
Section: Discussionmentioning
confidence: 66%
“…The review suggested that these interventions could help individuals develop a more balanced and less reactive relationship with their physical sensations, thereby alleviating somatic symptoms (Lakhan & Schofield, 2013). Additionally, Micheli et al (2022) conducted a community-based survey during the COVID-19 pandemic and found that mindfulness practices significantly reduced somatic symptoms and COVID-19-related anxiety, further supporting the utility of mindfulness in managing somatization (Micheli et al, 2022).…”
Section: Introductionmentioning
confidence: 96%